2017
DOI: 10.2147/oajsm.s113018
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of mesenchymal stem cells in human meniscal repair: current insights

Abstract: The menisci of the human knee play an important role in maintaining normal functions to provide stability and nutrition to the articular cartilage, and to absorb shock. Once injured, these important structures have very limited natural healing potential. Unfortunately, the traditional arthroscopic meniscectomy performed on these damaged menisci may predispose the joint toward early development of osteoarthritis. Although a very limited number of studies are available, mesenchymal stem cells (MSCs) have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Patients showed significant improvements in pain at 3 months and complications were limited to localized pain and swelling or tenosynovitis. A subsequent review by the same group reported that 32 of patients who had evidence of meniscal tears also demonstrated significant improvements in pain and function . They also reported on a 2014 case study in which a 32‐year‐old woman with a grade 2 medial meniscal tear in the posterior horn was injected with a similar combination of ASCs, PRP, hyaluronic acid, and calcium chloride, with 4 additional doses of PRP with calcium chloride and hyaluronic acid at days 3, 7, 14, and 28.…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 98%
“…Patients showed significant improvements in pain at 3 months and complications were limited to localized pain and swelling or tenosynovitis. A subsequent review by the same group reported that 32 of patients who had evidence of meniscal tears also demonstrated significant improvements in pain and function . They also reported on a 2014 case study in which a 32‐year‐old woman with a grade 2 medial meniscal tear in the posterior horn was injected with a similar combination of ASCs, PRP, hyaluronic acid, and calcium chloride, with 4 additional doses of PRP with calcium chloride and hyaluronic acid at days 3, 7, 14, and 28.…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 98%
“…In vitro and in vivo studies of clonally derived MSCs demonstrated that these cells consist of subsets that present different surface markers expression and different capacities for cellular differentiation [42]. These cells are considered a potential cell source for cell therapy since they can be easily collected from various tissues such as bone marrow [43], adipose tissue [44], synovial membrane [42], and amniotic membrane [45], among others. However, the equivalence of chondrogenic differentiation potential of MSCs derived from different tissues is a matter of considerable debate [46].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Successful repair strategies for lesions in the vascular zone of the meniscus like suturing have already been developed [ 17 , 18 ]. However, up to now, there is still no established curative therapy for lesions within the avascular parts of the meniscus in clinical practice [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the current literature, mesenchymal stromal cells (MSC) are the focus of attention in newly developed approaches for meniscus repair [ 2 , 21 27 ]. As these cells have both the potential to differentiate into fibrochondrocytes and the ability to secrete repair-promoting growth factors, they seem to be an ideal tool for meniscus repair [ 22 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation